La visión cristiana de los padres de Europa - Saiz, José Manuel (UNISCI Discussion Papers, 2007)
The original ideas of forming a united Europe arose from a christian vision of it, especially by Robert Schuman – already beatified by the Catholic Church, with his canonization in progress – and Alcide de Gasperi, with his beatification in progress. The Christian vision of both politicians is analyzed in this article, together with the ideas of Konrad Adenauer, the father of Germany’s postwar economic miracle, and Jean Monnet. These Christian ideas are in contrast with the writing of the current European Constitution that will complete the European integration process, from an economic perspective with the formation of an Economic and Monetary Union as well as, in the future, from a political one.